2011
DOI: 10.1099/vir.0.030163-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of acute and persistent Junín virus infections on the nucleo-cytoplasmic trafficking and expression of heterogeneous nuclear ribonucleoproteins type A and B

Abstract: Heterogeneous nuclear ribonucleoproteins A and B (hnRNPs A/B), cellular RNA-binding proteins that participate in splicing, trafficking, translation and turnover of mRNAs, have been implicated in the life cycles of several cytoplasmic RNA viruses. Here, we demonstrate that silencing of hnRNPs A1 and A2 significantly reduces the replication of the arenavirus Junín virus (JUNV), the aetiological agent of Argentine haemorrhagic fever. While acute JUNV infection did not modify total levels of expression of hnRNPs A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
(89 reference statements)
4
24
1
2
Order By: Relevance
“…Similar relocalizations of hnRNP A1, C1/C2, and K were also reported (24). In addition to VSV, other RNA viruses, such as enterovirus (25,26), rhinovirus (27), Japanese encephalitis virus (28), and Junin virus (29), have also been shown to relocalize hnRNP proteins. To the best of our knowledge, relocalization of hnRNP proteins by NiV infection has not been reported previously.…”
Section: Discussionsupporting
confidence: 51%
“…Similar relocalizations of hnRNP A1, C1/C2, and K were also reported (24). In addition to VSV, other RNA viruses, such as enterovirus (25,26), rhinovirus (27), Japanese encephalitis virus (28), and Junin virus (29), have also been shown to relocalize hnRNP proteins. To the best of our knowledge, relocalization of hnRNP proteins by NiV infection has not been reported previously.…”
Section: Discussionsupporting
confidence: 51%
“…The first report providing evidence about the importance of hnRNPs on JUNV replication was a comparative study of acute and persistent JUNV infections performed in Vero cell cultures [73]. Silencing of hnRNP A1 or hnRNP A2, by using small interfering RNAs (siRNAs), caused a decrease in JUNV protein synthesis and progeny virus production during acute infection.…”
Section: Cellular Proteins Involved In Rna Synthesis or Processingmentioning
confidence: 99%
“…These results indicate that hnRNP A1 would favor JUNV productive infection through the interaction with the nucleoprotein. On the other hand, JUNV non-productive persistent infection might involve downregulation of hnRNPs A/B, as well as changes in nucleo-cytoplasmic trafficking [73]. …”
Section: Cellular Proteins Involved In Rna Synthesis or Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This region contains potential recognition sites for RNA binding proteins (RBP), such as heterogeneous nuclear ribonucleoproteins (hnRNPs) (RBPmap [http://rbpmap.technion.ac.il/]). Interestingly, it has been reported that silencing of a number of hnRNPs, known to regulate translation, reduces virus yield in JUNV-infected cells, suggesting that hnRNPs might be required during infection (27,28). We speculate that the 5= conserved terminal motif (or eventually the terminal stem-loop) in concert with the internal UTR sequence harboring RBP recognition site(s) might facilitate the recruitment of the 43S preinitiation complex to viral mRNA.…”
Section: Discussionmentioning
confidence: 99%